CAMEL Method Assessment Model in Determining The Soundness Level Of Bank XYZ - Etty Susilowati; Pandu Adi Cakranegara; I Wayan Ruspendi Junaedi; Trie Hierdawati; Miftahorrozi Miftahorrozi (Enrichment : Journal of Management, 2022)
As a description of the state of the bank's performance and as a source of evaluation material for the government, particularly Bank Indonesia, it is highly important to evaluate the soundness of a bank. Maintaining the confidence of the general public throughout the process of making financial investments, saving money, applying for credit, and engaging in a variety of other pursuits is of the utmost importance. Each bank has the ability to establish its own category of soundness level. In this investigation, the method known as CAMEL is used to evaluate the soundness of the Bank's assessment model. CAMEL is an acronym that stands for Capital (C1), Asset Quality (C2), Management (C3), Equity (C4), and Liquidity. Each of these evaluation criteria has a specific set of evaluation criteria associated with it (C5). There are four distinct subcategories within the realm of bank soundness; these are as follows: unhealthy, less healthy, somewhat healthy, and healthy. The CAMEL method assessment model is applied to the case simulation, which consists of determining the soundness level of Bank XYZ based on the results of the financial performance evaluation. Because of this, the final value of the CAMEL method is 94.6, which can be categorized as a healthy level of the Bank.